2022
DOI: 10.1186/s12905-022-01891-y
|View full text |Cite
|
Sign up to set email alerts
|

How do nurses and midwives perceive their role in sexual healthcare?

Abstract: Background Nurses and midwives role in sexual healthcare is essential to help patients, particularly women, ensure a satisfactory sexual wellbeing. Yet, these professionals often overlook this aspect of patients’ health. Little is known regarding nurses and midwives’ attitudes, views and experiences concerning sexual healthcare. Using a naturalistic inquiry approach, this qualitative study was conducted to overcome this limitation and gain insights into nurses and midwives' role in the delivery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
1
3
0
3
Order By: Relevance
“…The study further stated that respondents believed that sexuality was important, but they were hesitant to talk about it because of taboos, ignorance, and widespread misconceptions (Pascual et al 2021 ). In support of this study, nurses’ negative attitudes towards sexual-related health information were also confirmed by an analogous study by Azar, Kroll and Bradbury-Jones ( 2022 ) who found that nurses felt uncomfortable as the subject is culturally regarded as a taboo and a sensitive one.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The study further stated that respondents believed that sexuality was important, but they were hesitant to talk about it because of taboos, ignorance, and widespread misconceptions (Pascual et al 2021 ). In support of this study, nurses’ negative attitudes towards sexual-related health information were also confirmed by an analogous study by Azar, Kroll and Bradbury-Jones ( 2022 ) who found that nurses felt uncomfortable as the subject is culturally regarded as a taboo and a sensitive one.…”
Section: Discussionsupporting
confidence: 80%
“…This study further revealed poor practices on the provision of health information regarding sexual activities. Consequently, the study by Azar et al ( 2022 ) advised inclusion of theoretical and clinical foundations of sexuality and sexual health in the nursing school curricula to enhance potential nurses’ competence about the provision of sexually related health education clients. In addition to these findings, only 47.8% of the participants guided patients and caregivers about the use of Warfarin information booklet.…”
Section: Discussionmentioning
confidence: 99%
“…Sexuality is considered a measure of an individual’s sense of well-being, fulfillment, and security. Moreover, as a measure of a couple’s well-being, harmonious sexual life is conducive to fostering a positive couple relationship [ 48 ]. On the contrary, sexual disorders may jeopardize family relationships [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…hemşirelerin cinsel sağlık konusunda eğitimlerinin olmamasını, cinsel sağlığın konuşulmasına engel olduğunu bildirmiştir. 24 Saunamäki ve ark. ise hemşirelerin 2/3'ünün hastaların cinsel kaygılarını konuşmada kendilerine güvenemediğini belirtmiştir.…”
Section: Discussionunclassified
“…17 Bu çalışmada ve yapılan diğer çalışmalarda, hemşireler kanser hastalarının hastalıkları nedeniyle cinsel problemler yaşadığının farkındadırlar ve cinselliğin tartışılmasının hastanın sağlığı için gerekli olduğuna inanmaktadırlar. 6,12,17,[24][25][26][27] Ancak hemşirelerin cinsel sağlık konusunda eğitimlerinin olmaması onların cinsel sağlık hakkında hastalarla görüşmelerinde kendilerini yeterli hissetmemelerine neden olmakta ve hemşireler bu konudaki iletişim sürecini başlatamamaktadır. Eğitim düzeyinin; cinsel sağlığa yönelik daha iyi tutum ve inanca sahip olmada, hastalarla iletişimi başlatabilmede önemli bir belirleyici olduğu bildirilmektedir.…”
Section: Discussionunclassified